(untitled) (The Journal of Nuwakot Adarsha Multiple Campus, 2025)
Background: Quality family planning (FP) services are essential for reducing unintended pregnancies, improving maternal and child health outcomes, and achieving Sustainable Development Goal 3.7. This study aimed to assess client satisfaction with FP services at Primary Health Care Centers (PHCCs) in Morang district and identify associated socio-demographic factors. Methods: A descriptive cross-sectional study was conducted from July to August 2018 among 196 female FP service clients recruited proportionally from seven PHCCs in Morang district. Data were collected using a structured questionnaire covering socio-demographic information and satisfaction indicators. Descriptive statistics (mean, SD, frequency, percentage) and linear regression were performed to examine associations between satisfaction and socio-demographic variables. Results: Participants’ mean age was 29.67 years, with the largest proportion aged 25–35 years (66.3%). Most respondents were Hindu (80.1%), and Brahmin/Chhetri (36.2%) was the dominant caste group. Housewives constituted 48% of the sample. Mean satisfaction scores were highest among those aged ≥35 years (38.91, SD=6.72) and respondents with primary education or below (39.36, SD=6.82). Regression analysis showed that non-Hindu participants reported significantly higher satisfaction (Coef = 4.22, p=0.007), whereas Janajati participants reported lower satisfaction than Brahmin/Chhetri (Coef = -3.30, p=0.029). No significant associations were observed with age, education, or occupation. Conclusion: Client satisfaction with FP services in Morang was significantly influenced by religion and caste rather than age, education, or occupation. Addressing social inequalities and ensuring inclusivity of marginalized groups is essential for improving FP service quality and equity in Nepal.